2020
DOI: 10.1186/s12889-020-8195-x
|View full text |Cite
|
Sign up to set email alerts
|

Community perspectives on barriers and challenges to HIV pre-exposure prophylaxis access by men who have sex with men and female sex workers access in Nigeria

Abstract: Background: Men who have sex with men (MSM), female sex workers (FSW) have critical needs for effective HIV prevention tools. This study identified perspectives of MSM, FSW and policy makers on the needs for, barriers to, and challenges with pre-exposure HIV prophylaxis (PrEP); and the logistics required to support roll-out of PrEP for MSM and FSW in Nigeria. Methods: Qualitative and quantitative data were collected through a cross-sectional study. The quantitative data were collected through an online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
5
49
2
Order By: Relevance
“…In this study, we document a higher LTFU rate than previously reported in the pre‐PrEP period (33.7 vs. 23.9 per 100 PY) [11]. While PrEP interest [2,17‐19], and uptake [16] among MSM in SSA is high, PrEP concentrations among 34 MSM and 8 TGW assessed six months following PrEP initiation was low [20], suggesting that MSM face challenges in sustained daily PrEP taking. Therefore, alternative strategies are needed to support daily PrEP taking and to retain participants in prevention services [21].…”
Section: Resultsmentioning
confidence: 65%
“…In this study, we document a higher LTFU rate than previously reported in the pre‐PrEP period (33.7 vs. 23.9 per 100 PY) [11]. While PrEP interest [2,17‐19], and uptake [16] among MSM in SSA is high, PrEP concentrations among 34 MSM and 8 TGW assessed six months following PrEP initiation was low [20], suggesting that MSM face challenges in sustained daily PrEP taking. Therefore, alternative strategies are needed to support daily PrEP taking and to retain participants in prevention services [21].…”
Section: Resultsmentioning
confidence: 65%
“…In Kenya, it was found that 64.3% of participants had heard of PrEP and only half were willing to use it [ 17 ]. Several barriers were described by authors, such as stigma, cost, frequency of HIV counselling and treatment and possible drug interactions; concerns included the possible abandonment of condoms, increased risk of sexually transmitted infections, and non-compliance with medications and schedules, which need to be taken into account when setting up a PrEP programme [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing need to better understand how Facebook's advertising platform could be used to recruit participants based in African countries. A bulk of web-based studies in African countries have recruited participants mostly through snowball samples of university students [18][19][20][21] and men who have sex with men [22]. In some cases, the recruitment group was comprised of medical practitioners such as physicians [23,24] and public health officials [25].…”
Section: Introductionmentioning
confidence: 99%